The EPSRC's responsible innovation framework: to what extent does it influence research practice? - Rose, David Christian; Shortland, Faye; Smith, Rachel; Schillings, Juliette (Cranfield University, 2023)
The world is on the cusp of a technology revolution in which radical technologies (e.g. AI, robotics, drones) offer the potential to transform society. The UK Government has committed to driving this through their Industrial Strategy, much of it distributed through UK Research Councils, to achieve aims such as Transforming Food Production and Clean Growth. It has been argued that responsible innovation principles - anticipation, inclusion, reflexivity, and responsiveness - should be embedded within this technology revolution so that the benefits, opportunities, and risks are properly considered. To this end, funders such as EPSRC are committed to responsible innovation. Yet, there has been little empirical work which investigates whether responsible innovation training actually changes design practices. Through surveys and interviews of EPSRC-funded researchers and PhD students, this pilot project investigates the impact of their responsible innovation framework (AREA) on research in practice.
Keywords: Science and Technology Studies; Responsible Innovation